Body Below the Train: An Autopsy in Vain? A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Autopsy surgeons in India encounters vast varieties of cases, among them most of the fatal cases are due to heavy machine trauma either due to road accidents or railway-associated injuries. The most common manner of death in these cases is accidental. However, it is quite difficult to designate a case of road side or railway-associated incident as a homicidal due to run over injuries resulting into non-availability of intact soft tissue and bone so that one can differentiate between ante-mortem and post-mortem injuries. Railway-associated injuries are sometimes used to conceal the homicidal manner of death. In such cases, the autopsy surgeon should look for the injuries which are not in accordance with the history and circumstantial evidences with investigation report should be given due credence in such cases. One such case we are discussing here in which the homicidal manner of death was projected as an accident in which thorough examination of the body revealed the manner of death as homicidal.
Keywords: Disintegration; Railway-associated injuries; Homicide, Autopsy